Heparin-hidden pillar in the management of burns - Cacique, Mauricio D.; Alvarado, Ricardo L.; A., Maria del Carmen; Armenta, Dania Báez; Diaz, Oscar F. F.; Azcué, Arsenio F. A. (International Journal of Research in Medical Sciences, 2024)
Heparin has been used to treat burns for decades, but due to the lack of well-controlled clinical trials, this indication is little widespread and the calculation of dosage and application method becomes unclear. Its action on the burn is probably derived from its anti-inflammatory and angiogenic properties that do not depend on its known anticoagulant action, at the endothelial level, it reduces blood hyperviscosity, leukocyte count and acute phase reactants, and also reduces the need for escharotomies, fasciotomies and grafts. In the present study we confirmed that the use of topical heparin reduces healing time, epithelialization, as well as local discomfort, it can be used in second level hospitals not specialized in burns due to its easy systemic and topical application, being safe, which showed few complications despite being administered at high doses.